The corrosion effect to metal structure influenced by microbial at oil and gas plant - Wan Jusoh, Wan Amizah; Che Rosely, Noor Ain Najihah; Adnan, Suraya Hani; Mohd Zuki, Sharifah Salwa; Shahidan, Shahiron (Penerbit UTHM, 2022)
Corrosion is the destructive attack of metal on its surroundings by chemical or electrochemical reactions. There are four common types of corrosion problems occurred on the pipelines of oil and gas plants. Those are (i) sour corrosion, (ii) oxygen corrosion, (iii) stress corrosion cracking and (iv) microbiologically induced corrosion. In order to keep the metal structures of oil and gas plants resistant to corrosion, carbon steels are undeniably the best materials to use for pipelines. As for microbiologically induced corrosion, there are two types of it, (i) Sulphate-Reducing Bacterium and (ii) Sulphur-Oxidizing Bacterium. There will be negative consequences to the oil pipelines affected by microbiologically induced corrosion and will be explained vigorously on the next page. Electrochemical, physical and chemical techniques are those different treatments that can be used to dwindle the corrosion from the metal structures of pipelines in oil and gas plants. The solution to identify corrosion caused by microbial is by using electrochemical techniques. By using this technique, the potential mechanism of microbially influenced corrosion of steel by marine bacterium Vibrio natriegens. Cathodic protection using sacrificial anodes is practical and globally applied to prevent corrosion, while electrochemical techniques can determine the mechanism of MIC. Through the methods, the objective of this study has been achieved.